Enhancing Approach for Information Security in Hadoop - Raghad Z. Yousif; Shahab W. Kareem; Shadan M. Abdalwahid (Polytechnic Journal)
Developing a confident Hadoop essentially a cloud computing is an essential challenge as the cloud. The protection policy can be utilized during various cloud services such as Platform as a Service (PaaS), Infrastructure as a Service (IaaS), and Software as a Service (SaaS) and also can support most requirements in cloud computing. This event motivates the need of a policy which will control these challenges. Hadoop may be a used policy recommended to beat this big data problem which usually utilizes MapReduce design to arrange huge amounts of information of the cloud system. Hadoop has no policy to ensure the privacy and protection of the files saved within the Hadoop Distributed File System (HDFS). Within the cloud, the safety of sensitive data may be a significant problem within which encryption schemes play an avital rule. This paper proposes a hybrid method between pair wellknown asymmetric key cryptosystems (RSA and Rabin) to cipher the files saved in HDFS. Therefore, before storing data in HDFS, the proposed cryptosystem is employed to cipher the information. In the proposed system, the user of the cloud might upload files in two ways, secure or non-secure. The hybrid method presents more powerful computational complexity and smaller latency as compared to the RSA cryptosystem alone.